MoodLift – A Mobile Application for Mental Health - Mohd Fadil, Muhammad Syafiq (2022)
The main goal of this final year project is to develop a mobile application to provide assistance to people with mental health issues such as depression, caused by elevated stress, anxiety and severe levels of loneliness caused by the COVID-19 pandemic quarantine and self-isolation.